Activities of Methanol Extracts of the Leaves of Morinda Citrifolia Against Freshwater Fish Bacterial Pathogens - MUTHULAKSHMI.G; NEELANARAYANAN.P (International Journal of Pharma and Bio Sciences, 2018)
The present study reports screening of phytochemical constituents and antibacterial activities of methanol leaves’ extracts of Morinda citrifolia. The leaves’ extracts had the following phytochemical compounds such as, Alkaloids, Phenols, Tannins, Saponins, Terpenoids, Flavonoids, Oils, Resins, Gums, Carbohydrates and Amino acids. The antibacterial activities of these extracts of M. citrifolia were tested against five pathogenic bacteria namely Escherichia coli, Streptococcus aureus, Klebsiella pneumonia, Pseudomonas aeruginosa and Salmonella paratyphi A. The extract exhibited antibacterial activities against all the selected bacterial pathogens even at minimum concentration. The maximum antibacterial activity was found against Klebsiella pneumonia (3.66± 0.33) at 500 μg/ml concentration. It is concluded that the leaves’ extract of M. citrifolia may be used as therapeutic agents against fish pathogens.